Real-world Study on the Effect of PARPi as Maintenance Therapy on Platinum Sensitivity after First- and Second-line Chemotherapy in Patients with Recurrent High-grade Serous Epithelial Ovarian Cancer - Guo, Yanglong; Chen, Xi; Tang, Xuedong; Pan, Shan; Zhu, Tao; Zhang, Yingli (Current Cancer Drug Targets, 2024)
Background: This study investigated the effect of poly(ADP-ribose) polymerase inhibitors (PARPi) as maintenance therapy after first- and second-line chemotherapy on platinum sensitivity in patients with recurrent high-grade serous epithelial ovarian cancer (rHGSOC). Methods: This study retrospectively analyzed 172 patients with rHGSOC treated at Zhejiang Cancer Hospital and Jiaxing Maternity and Child Health Care Hospital between January 2017 and December 2021. The 1st-PARPi group comprised patients who received a PARPi as maintenance therapy after first-line chemotherapy (n=23), and the 1st-control group comprised those who did not (n = 105). Similarly, the 2nd-PARPi group comprised patients not given a PARPi in their first-line treatment (n = 30), and the 2nd-control group comprised those who were given a PARPi (n = 89). Results: Among the 23 patients in the 1st-PARPi group and the 105 patients in the 1st-control group, nine and 99 were platinum-sensitive, and 14 and six were platinum-resistant, respectively (hazard ratio [HR]: 14.46, P < 0.0001). Among the 30 patients in the 2nd-PARPi group and 89 patients in the 2nd-control group, 10 and 71 were platinum-sensitive, and 20 and 18 were platinumresistant, respectively (HR: 4.37, P < 0.0001). Age, stage, residual tumor, the courses of platinumbased chemotherapy, and breast cancer susceptibility gene mutations were not associated with platinum sensitivity when using a PARPi as maintenance therapy after first- and second-line chemotherapy. Conclusion: Patients with rHGSOC using a PARPi were more likely to be platinum-sensitive and develop platinum resistance independent of PARPi duration. Care should be taken when using a PARPi as maintenance therapy after first- and second-line chemotherapy.
Keywords: PARP inhibitor